2020
DOI: 10.1088/1751-8121/ab81d8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a delayed predator–prey interaction incorporating nonlinear prey refuge under the influence of fear effect and additional food

Abstract: The main object of this work is to analyse the impacts of fear effect on the dynamics of predator-prey interaction incorporating non linear prey refuge to control the extinction of predator. We have taken a Holling type II functional response in presence of additional food. The positivity and uniform boundedness of solutions have been discussed. The feasibility conditions of all equilibrium points and their stability behaviours are derived. Next, we have studied the existence of local bifurcation (transcritica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Existence Here d [TC] criteria and stable behaviour of all the biologically meaningful equilibria have been discussed. It has to be noted that Hopf bifurcations are exhibited around E 3 (subsidy free) and E * (interior) of system (2) considering k as a bifurcating parameter (see 9,11,and 12). Also, observing Figures 6 and 12, it can be concluded that high levels of fear can stabilize system (2) by excluding the existence of periodic solutions.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Existence Here d [TC] criteria and stable behaviour of all the biologically meaningful equilibria have been discussed. It has to be noted that Hopf bifurcations are exhibited around E 3 (subsidy free) and E * (interior) of system (2) considering k as a bifurcating parameter (see 9,11,and 12). Also, observing Figures 6 and 12, it can be concluded that high levels of fear can stabilize system (2) by excluding the existence of periodic solutions.…”
Section: Discussionmentioning
confidence: 90%
“…In 2020, Mondal and Samanta [11] analyzed the dynamics of a delayed predator-prey interaction incorporating nonlinear prey refuge function under the influence of fear effect and additional food. Motivated by the work of Mondal and Samanta [11], we have first considered a predator-preysubsidy model with nonlinear prey refuge function where the prey and subsidy occur in the same habitat and they are both consumed by a single generalist predator according to the following differential equations:…”
Section: Model Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is used to describe the dynamic distribution of population density produced by the interaction of the species in the ecosystem or the surrounding environment. In particular, the interaction of the predator-prey system is one of the basic structures in complex ecosystems, and such models have been widely studied (see [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]) under the uniform condition of the space, in other words, all coefficients of the model are positive. Because the natural environment of most species is spatially heterogeneous, biologists and mathematicians believe that the inhomogeneity of the spatial environment has a significant impact on the dynamic behavior of the biological population system, which is confirmed by the biologist C. B. Huffaker's biological experiment.…”
Section: Introductionmentioning
confidence: 99%